2017
DOI: 10.1039/c6ra24978g
|View full text |Cite
|
Sign up to set email alerts
|

The study of complexation between dicationic surfactants and the DNA duplex using structural and spectroscopic methods

Abstract: Dicationic (also known as gemini or dimeric) bis-alkylimidazolium surfactants belong to a group of non-viral transfection systems proposed for the successful introduction of different types of nucleic acids (i.e., siRNA, DNA oligomers, and plasmid DNA) into living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(120 reference statements)
2
9
0
Order By: Relevance
“…The results of the gel electrophoresis experiment indicated better complexing properties of surfactants towards siRNA (for most of them at p/n = 1.5) than dsDNA. A similar effect has been observed previously for the lipoplexes obtained on the basis of imidazolium dichlorides [29,30]. A significant effect of the length of the spacer group of the studied surfactants on the binding efficiency of nucleic acid oligomers was observed.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the gel electrophoresis experiment indicated better complexing properties of surfactants towards siRNA (for most of them at p/n = 1.5) than dsDNA. A similar effect has been observed previously for the lipoplexes obtained on the basis of imidazolium dichlorides [29,30]. A significant effect of the length of the spacer group of the studied surfactants on the binding efficiency of nucleic acid oligomers was observed.…”
Section: Discussionsupporting
confidence: 87%
“…The CD spectra deformations indicate significant conformation changes and the levorotatory character of the oligomer, which is directly related to deterioration of the complexing abilities. The changes in CD curves were similar to those taking place upon the transition of B-DNA to Z-DNA or X-DNA [35,52,53,54] which has been observed earlier for the mixtures of dsDNA with imidazolium surfactant [30].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Efforts have been made to design novel QAS for gene delivery that would be able to deliver nucleic acids without complementary action of helper lipids. Inspired by rigid, planar structure of Chol, Andrzejewska et al synthetized cationic gemini surfactants that comprise a rigid cyclic moiety and condensed DNA of various length into stable aggregates, being the surfactant with longer spacer slightly more efficient in DNA binding [129].…”
Section: Quaternary Ammonium Surfactants In Pharmaceutical Applicamentioning
confidence: 99%
“…Particular attention is paid to the flexibly or rigidly linked bisimidazolium salts, the so-called gemini ILs. Gemini ILs can show interesting surfactant and liquid crystalline properties [ 4 12 ] and such salts were used in many applications, ranging from catalysis [ 13 ] to biological [ 14 16 ] or biochemical applications [ 17 19 ]. Recently, we have shown that it is possible to exchange the smaller anions (Br − ) with alkyl sulfate ions to yield new ILCs based on bisimidazolium salts with flexible methylene spacer and long alkyl tails [ 20 ].…”
Section: Introductionmentioning
confidence: 99%